Hedging In Indonesian Sharia Stock Index Manufacturing Companies - Hilmy Baroroh; Sarpiatun Hasanah (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - This study aims to determine the influence of financial distress, profitability, and liquidity on hedging activities in manufacturing companies listed on the Indonesian Sharia Stock Index during the period 2016-2020.Method - The analysis in this study uses logistic regression analysis to answer the research questions. The study utilizes purposive sampling technique to determine the sample, and total of 80 samples are obtained from manufacturing companies listed on the Indonesian Sharia Stock Index during the period of 2016-2020.Result - The results of this study that financial distress, proxied by the Altman Z-score model, does not have a significant effect on hedging activities in manufacturing companies. On the other hand, profitability, proxied by return on assets, has a positive and insignificant effect on hedging activities in manufacturing companies, while liquidity, proxied by the current ratio, has a negative and significant effect on hedging activities in manufacturing companies.Implication - In this study, uses secondary data obtained from the annual report and financial reports of manufacturing companies listed on the Indonesian Sharia Stock Index during the period 2016-2020.Originality - Future research is expected to be able to add or replace different proxies, particularly those related to financial distress, will be utilized in the theory of hedging activities. This will expand the discussion on the determinants of hedging policy in manufacturing companies in Indonesia.